Early Intervention in Psychosis Treatment Components Utilization in Patients Aged Over 35 - Jagger, Grace; de la Fuente-Tomas, Lorena; Stochl, Jan; Allan, Sophie M; Clay, Felix; Kenedler, Lizzie; Treise, Cate; Perez, Jesus (Community mental health journal, 2020)
Early Intervention in Psychosis (EIP) services have been youth-focused since their inception. In England, recent National Institute for Health and Care Excellence (NICE) guidelines and new National Health Service (NHS) Standards for EIP recommend the expansion of the age acceptability criterion from 14-35 to 14-65. In the Cambridgeshire and Peterborough EIP service (CAMEO), we ran a service evaluation to assess the initial impact of this policy change. It aimed to elicit EIP treatment components utilization by patients with first-episode psychosis (FEP) aged over 35, in comparison with those under 35. We found that the over-35s required more contacts from EIP healthcare professionals, especially from care coordinators (coefficient = .239; Robust SE = .102; Z = 6.42; p = 0.019) and social workers (coefficient = 18.462; Robust SE = .692; Z = .016; p < 0.001). These findings indicate that FEP patients aged over 35 may present with more complex and sustained clinical/social needs. This may have implications for EIP service development and commissioning.
Keywords: Anglie; Adolescent; státní lékařství; Mental Health Services; časná lékařská intervence; State Medicine; lidé; senioři; psychotické poruchy; Aged; Early Medical Intervention; England; mladiství; Psychotic Disorders; služby péče o duševní zdraví; Humans